The Aesthetic Principle and its relation to human beings. On the anthropologic dimension of the Aesthetics of Alexander Baumgarten - del Valle, Julio (Estudios de Filosofía, 2008)
The presentation of the original sense with which Aesthetics was born as a Philosophical Discipline, in Alexander Baumgarten ́s work, is the central axis of this article. It has three parts. First, with the aim of historically contextualizing the birth of Aesthetics, has as its basic idea that The Illustration is a movement with European roots and with a preeminent anthropological aspect. The second part focuses on presenting and explaining the central concepts of Baumgarten ́s Aesthetics, that is, that it is a re ection on the Particular as Particular. The third relates the Aesthetic Reflection with the Human Dimension. The basic idea of this third part, which gives sense to the whole article, is that Baumgarten ́s Aesthetic is directed to the Construction of a Complete Human Being, the person that knows how to integrate reason and sensibility, and finds in such integration a happy harmony. This human being will be called the felix aestheticus.